PROFESIONALISNE ANGGOTA KEPOLISIAN DALAM PENEGAKAN HUKUM (Solusi, 2023)
The aim of this research is to find out the efforts to improve quality and prevent Polri's professionalism in carrying out police duties. This research is a normative legal research with a statutory approach. The material obtained in the study was collected through data collection methods, namely. the library research approach which is the only method in legal normative research, and this research also uses secondary data, which has the ability to connect and differentiate: primary material, secondary material and tertiary legal material. The results of the study show that the factors that influence police professionalism include: legal factors, law enforcement factors, budgetary factors and infrastructure factors. The realization of professionalism is reflected in the management of police duties by increasing the service and quality of investigations by members of the investigation unit, as well as increasing the technical knowledge and skills of police officers who have post-training and police specialist training, their competence. and technical police knowledge increases, which facilitates their law enforcement duties in society.